Peranan Bea dan Cukai dalam Pengawasan Barang Bawaan Penumpang (Non-Personal Use) dari Luar Negeri ke Daerah Free Trade Zone - Andre Argadho Tampubolon; Fadlan Fadlan; Christiani Prasetiasari; Ramon Nofrial (Penerbit Goodwood, 2023)
Purpose: The aim of this research is to determine the legal regulations for users of expedition services for goods that cannot be released by customs and excise officers in the Free Trade Zone (FTZ) area and how they are implemented, obstacle factors, and efforts of users of expedition services for goods. Research methodology: The research method for this thesis is normative juridical (legal research) through a literature study with an empirical juridical approach (sociological juridical) through field studies aimed at gaining legal knowledge. Results: The research results show that legal regulations for expedition service users in the case of goods that cannot be released by Customs and Excise officers in the Free Trade Zone (FTZ) area are regulated based on Article 16 of Law Number 17 of 2006 concerning Customs and Article 20, paragraph ( 1) Regulation of the Minister of Finance of the Republic of Indonesia Number:199 /PMK.Ol0/2019 concerning Customs, Excise, and Tax Provisions for the Import of Shipped Goods, which regulates actions to detain shipped goods that do not pay the customs tariff and value as determined. Implementation of expedition service users for goods that cannot be released by Customs and Excise officers in the Free Trade Zone (FTZ) area, as observed at PT. Batam Branch Logistics Trade Ambassador, demonstrated the complexity involving laws, procedures and economic challenges Limitation: This study highlights the legal regulations and implementation process for expedition service users in the Free Trade Zone (FTZ) area with regard to goods that cannot be released by customs and excise officers. Contribution: Overall, this research makes a significant contribution to the understanding of the legal framework and practical issues surrounding the use of expedition services in the FTZ area.